COMPARATIVE STUDY OF MASS MEDIA VOCABULARY IN ENGLISH AND UZBEK - Sotvaldiyeva Hilola Musinovna; Tillavoldiyev Rustamjon Kholmatjon ugly (Zien Journals, 2022)
This article is about the style of language used in the media, and it briefly touches on the media and the term "medialinguistics". Also, the criterias of medialinguistics are presented and explained in both languages: English and Uzbek. The article also briefly covers the efforts, successes and shortcomings in this field.
Keywords: mass media; linguistic methodology; speech; linguistics